2020
DOI: 10.1681/asn.2019060575
|View full text |Cite
|
Sign up to set email alerts
|

Bundled Payment Reform and Dialysis Facility Closures in ESKD

Abstract: BackgroundIn 2011, inclusion of injectable medications into an expanded ESKD payment bundle prompted concerns that dialysis facilities facing higher costs might close, disrupting care delivery and access to care. Whether this policy change influenced dialysis facility closures is unknown.MethodsTo examine whether facility closures increased after 2011 and whether factors influencing closures changed, we analyzed US Renal Data System registry data to identify all patients receiving in-center hemodialysis from 2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
21
0
2

Year Published

2020
2020
2021
2021

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 12 publications
(24 citation statements)
references
References 23 publications
(19 reference statements)
1
21
0
2
Order By: Relevance
“…Despite this 1-time increase in dialysis facility acquisitions associated with policy reform, no significant changes in longer-term acquisition trends were noted. Similar to a previous analysis, 6 dialysis facility closures were relatively infrequent over the 10-year study period and did not change in association with reimbursement reform. Trends in acquisitions and, to a lesser extent, closures corresponded with an increase in the proportion of all dialysis facilities operated by large dialysis organizations from 69% in 2006 to 85% in 2016.…”
supporting
confidence: 80%
“…Despite this 1-time increase in dialysis facility acquisitions associated with policy reform, no significant changes in longer-term acquisition trends were noted. Similar to a previous analysis, 6 dialysis facility closures were relatively infrequent over the 10-year study period and did not change in association with reimbursement reform. Trends in acquisitions and, to a lesser extent, closures corresponded with an increase in the proportion of all dialysis facilities operated by large dialysis organizations from 69% in 2006 to 85% in 2016.…”
supporting
confidence: 80%
“…3,6,25,30,31 These strategies all have the potential to reduce access to quality care and worsen clinical outcomes. 3,[5][6][7]12 Policy makers should be aware of the facility-and market-level characteristics that are most strongly associated with acquisitions and closures. Market size and HHI were not associated with acquisitions and had minimal association with closures.…”
Section: Yearmentioning
confidence: 99%
“…In the run-up to the PPS, dialysis organizations, both large and small, warned of impending facility closures, decreased access to care, and increased consolidation. 9 , 10 To date, studies have shown that the number of unique dialysis facilities actually increased after 2011, 11 , 12 while facility closures declined. 12 Most facilities have adapted to the PPS by instituting clinical and organizational changes such as lowering the doses of expensive injectable medications and modestly increasing the provision of historically less expensive dialysis modalities (eg, peritoneal dialysis).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…There is little evidence that the 2004 reform of the Monthly Capitation Payment led to a measurable improvement in the quality of care delivered to patients 4 . In addition, bundled payment reform in 2011 was not found to consistently lead to dialysis facility closures 5 …”
Section: Introductionmentioning
confidence: 99%